Contemporary Missions Issues: Toward Renewing a Commitment to Partnership - Snider, William (Asian Journal of Pentecostal Studies, 2022)
The article discusses partnership in the Philippines ties to evangelize and disciple, plant churches, train workers and conduct ministries of social concern. It mentions international mission partnerships struggle in praxis due to a lack of emphasis on a Biblical theology of partnership, which in turn is due to a lack of understanding the necessity of relationships based on mutuality.